Increased rod stiffness improves the degree of deformity correction by segmental pedicle screw fixation in adolescent idiopathic scoliosis - Abul-Kasim, Kasim (BioMed Central, 2011)
BACKGROUND: There are limited reports in literature studying the impact of rod diameter and stiffness on the degree of deformity correction in patients with AIS. AIMS: The aims of this study were to evaluate the 3-dimentional deformity correction achieved by segmental pedicle screw fixation in patients with adolescent idiopathic scoliosis, and to find out if learning or the change to stiffer rods had any positive impact on deformity correction. STUDY DESIGN: Retrospective study. METHODS: Plain radiographs and low-dose spine CTs of 116 consecutive patients (aged 15.9 ± 2.8 years) operated during the period 2005-2009 (group 1: patients operated autumn 2005-2006; group 2: 2007; group 3: 2008; group 4: 2009) were retrospectively evaluated. RESULTS: There was no statistically significant difference between the correction of the Cobb angle (P = 0.425) or lower end vertebra tilt (P = 0.298) in patients operated during the first versus the remaining periods of the study. No restoration of the sagittal kyphosis was reported in the first period compared with 5.9° in the last study period (P < 0.001). The correction of vertebral rotation was also improved from 4.2° to 7.8° (P < 0.001) for the same periods. For the whole study population, there was statistically significant correlation between the order of the operation (patient number) and the restoration of sagittal kyphosis (r = -0.344, P = 0.001), and the correction of vertebral rotation (r = 0.370, P < 0.001), but not for the Cobb angle or LEVT. However, there was no significant difference in restoration of sagittal kyphosis and the vertebral rotation in the first 17 patients compared with the last 17 patients operated with rods of 5.5 mm diameter (P = 0.621, and 0.941, respectively), indicating that rod stiffness had more impact on the deformity correction than did learning. CONCLUSIONS: This study showed that rod stiffness had more impact on the deformity correction than did learning.